Determinant Analysis of Muslim Communities Consuming Products Halal Labeled in Bangkalan Regency - Mashudi , Mashudi; Dahruji , Dahruji; Yakubu , Abubakar (Al-Insyiroh: Jurnal Studi Keislaman, 2023)
Products labeled halal are products that have been declared halal according to Islamic law and stipulated by the Ministry of Religion through the Halal Product Assurance Agency (BPJPH) based on the results of an inspection by LPPOM MUI of the product in question, with this product labeled Halal it can meet market demands (consumers). ) universally. So if these demands can be met, economically, Indonesian business people will be able to become hosts in terms of the products being marketed. Not only that, having products labeled halal can protect the faith of consumers, especially those who are Muslim. This means that with labeling, Muslim consumers will no longer hesitate to consume something they need.Researchers used a Quantitative approach to conduct this research. This study aims to find out what factors influence Muslim communities to consume products labeled halal in Bangkalan Regency. There are several factors that can influence Muslim consumers to consume the halal label, such as religious factors, psychological factors, family factors, role and status factors, social factors, and cultural factors. The results of this research later we can find out what factors are more prominent among several existing factors that make the Muslim community in Bangkalan Regency consume products with a halal label.The results of this study from the ten initial factor variables used in this study, after analysis using factor analysis, three new factors were formed, namely: factor 1 is called the credibility factor, with the 3 members being religion, role and status, and social culture. Factor 2 is named as the knowledge factor, with the 5 members being Psychological, Family, Needs, Recommendations, Knowledge. Factor 3 is called a lifestyle factor, with the 2 members being health and lifestyle